Political quietism in Islam : Sunni and Shīʻī practice and thought - Sarḥān, Saʻūd ibn Ṣāliḥ (Markaz al-Malik Fayṣal lil-Buḥūth wa-al-Dirāsāt al-Islāmīyah (Series), 2020)
"In recent years, Islam - whether via the derivatives of 'Political Islam' or 'Islamism' - has come to be seen as an 'activist' force in social and political spheres worldwide. What such representations have neglected is the strong countervailing tradition of political quietism. Political quietism in Islam holds that it is not for Muslims to question or oppose their leaders. Rather, the faithful should concentrate on their piety, prayer, religious rituals and personal quest for virtue. This book is the first to analyze the history and meaning of political quietism in Islamic societies. It takes an innovative cross-sectarian approach, investigating the phenomenon and practice across both Sunni and Shi'i communities. Contributors deconstruct and introduce the various forms of political quietisms from the time of the prophetic revelations through to the contemporary era. Chapters cover issues ranging from the politics of public piety among the women preachers in Saudi Arabia, through to the legal discourses in the Caucasus, the different Shi'i communities in Iran, Lebanon, Iraq and Pakistan, and the Gulen movement in Azerbaijan. The authors describe a wide range of political quietisms and assess the continuing significance of the tradition, both to the study of Islam and to the modern world today."--